Distribusi Panas Pengereman pada Sistem Rem Tromol - Faisal Amri; Wanda Afnison; Toto Sugiarto; Wagino Wagino (Universitas Negeri Padang, 2023)
This study discusses the distribution of heat in the drum brake system using the experimental method using drums as the braking medium. The test was carried out using the brake test prototype process with the application of press and release. The test data collection technique is using three methods, namely by applying the same amount of press and release of the brake (20 seconds of pressure and 20 seconds of release), the application of press and release of the brake is released more than pressed (30 seconds is released and 10 seconds is pressed), and the application of press and release is more pressed than released (20 seconds pressed and 10 seconds released). The results showed that the highest temperature obtained in the application of brakes for 20 seconds and release for 20 seconds on standard drum brakes reached 61.8 º C, while applying the brakes for 10 seconds and releasing them for 30 seconds reached 46.3 º C, and applying the brakes for 20 seconds and releasing them for 10 seconds achieved a temperature increase of 73.5 º C. Penelitian ini berdiskusi tentang distribusi panas pada sistem rem tromol dengan metode eksperimen menggunakan tromol sebagai media pengereman. Adapun teknik pengambilan data pengujian yaitu dengan tiga metode, yaitu dengan pengaplikasian tekan dan lepas rem sama banyak (20 detik tekan dan 20 detik lepas), pengaplikasian tekan dan lepas rem lebih banyak dilepas dari pada ditekan (30 detik dilepas dan 10 detik ditekan), dan pengaplikasian tekan dan lepas rem lebih banyak ditekan dari pada dilepas (20 detik ditekan dan 10 detik dilepas). Hasil penelitian menunjukkan suhu tertinggi yang didapatkan pada pengaplikasian rem selama 20 detik dan lepas selama 20 detik pada rem tromol standard mencapai 61,8oC, sementara pengaplikasian rem 10 detik dan lepas selama 30 detik mencapapi 46,3oC, dan pengaplikasian rem 20 detik dan lepas selama 10 detik mencapai kenaikan suhu 73,5oC.